Estimation of Copper and Cadmium Bioavailability in Contaminated Soil Remediated by Different Plants and Micron Hydroxyapatite - Lei Xu; Xiangyu Xing; Jianbiao Peng; Mingfei Ji (Bioinorganic Chemistry and Applications)
A three-year in situ remediation experiment was carried out to understand the effect of combined phytoremediation with chemical materials on the bioavailability of heavy metals in soil. Indigenous weed (Setaria pumila), energy plant (Pennisetum sp.), cadmium (Cd)-hyperaccumulator (Sedum plumbizincicola), and copper (Cu)-tolerant plant (Elsholtzia splendens) were used as the phytoremediation plants aided by micron hydroxyapatite (1% wt). The bioavailability of Cu and Cd in soil was evaluated during the three years. The results showed that the four plants combined with micron hydroxyapatite significantly increased soil pH and soil organic carbon (SOC), and decreased Cu and Cd fractions extracted by CaCl2 and diffusive gradients in thin films (DGT) than the untreated soils, respectively. Because of the large biomass, the accumulation of Cu and Cd is the largest in Pennisetum sp. followed by Elsholtzia splendens, Sedum plumbizincicola, and Setaria pumila. The bioavailability of Cu and Cd is significantly negatively correlated with pH, soil organic carbon, available phosphorus, and available potassium. Moreover, the correlation is mainly related to the addition of micron hydroxyapatite. The accumulation of Cu and Cd is the combined action of the soil bioavailability of Cu, Cd, and biomass. Our results suggest that Pennisetum sp. can act as an appropriate remediation plant for phytoremediation aided by amendments.